2017
DOI: 10.1186/s12889-017-4266-z
|View full text |Cite
|
Sign up to set email alerts
|

National Alcohol Survey of households in Trinidad and Tobago (NASHTT): Alcohol use in households

Abstract: BackgroundTo determine the patterns of alcohol use among households in Trinidad and Tobago (T&T) and to estimate the association between alcohol use and negative psychological, social, or physical events experienced by the household.MethodsA convenience sample of 1837 households across T&T. We identified bivariate correlates of alcohol use, and heavy episodic drinking using chi-square and t-test analyses and used multivariable logistic regression to estimate adjusted associations between household alcohol use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In line with the country's drinking patterns, having a last‐year, last‐month and HED drinker member was very common in Vietnamese households. Prevalence of households having a HED drinker in Vietnam was much higher than that (30.4%) of a study sharing the same measurement in Trinidad and Tobago .…”
Section: Discussionmentioning
confidence: 99%
“…In line with the country's drinking patterns, having a last‐year, last‐month and HED drinker member was very common in Vietnamese households. Prevalence of households having a HED drinker in Vietnam was much higher than that (30.4%) of a study sharing the same measurement in Trinidad and Tobago .…”
Section: Discussionmentioning
confidence: 99%
“…Over the years this community has seen an increase in violent crimes, many linked to drug and alcohol use. Also many HH are affected by intimate partner violence and the effects of alcohol abuse [ 17 ]. This idea of second-hand drinking has support in the literature, in this case persons who experienced family or personal aggressive harms or who were concerned about a relative’s drinking were more supportive of restrictive alcohol policies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5 domains were: The HH’s use of alcohol The social, medical and psychological impact of alcohol use on the respondent’s immediate HH, family members or relatives, friends or co-workers. The results of the survey findings of these first 2 domains have been published [ 17 ]. The HH’s impression of the impact of the alcohol trade on their immediate residential environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…National Alcohol Survey of households in Trinidad and Tobago (NASHTT): Alcohol use in households‖ (Maharaj et al, 2017) The researcher used standard descriptive statistics to characterize the study population and reported alcohol use within the past year at the household level. The result is approximately two-thirds of households in T&T reported using alcohol.…”
Section: Previous Studiesmentioning
confidence: 99%